Fullerene Network‐Buffered Platinum Nanoparticles Toward Efficient and Stable Electrochemical Ammonia Oxidation Reaction for Hydrogen Production - Chen, Xiang; Ke, Zhongyuan; Wang, Xing; Jin, Hongqiang; Cheng, Yuwen; Xiao, Yukun; Jiang, Rui; Da, Yumin; Fan, Lei; Li, Hexing; Liu, Dongming; Yang, Shangfeng; et al. (Angewandte Chemie International Edition, 2025)
Green ammonia is a promising hydrogen carrier due to its well‐established production, storage, and transportation infrastructure. Moreover, hydrogen production via electrochemical ammonia oxidation reaction (AOR) requires a significantly lower theoretical potential than water electrolysis. However, the sluggish kinetics and poor stability of AOR hinder the industrial application of ammonia electrolysis. Herein, we report the construction of two‐dimensional covalently bonded fullerene polymeric network (PNW‐C60) supported platinum nanoparticles (Pt NPs) as a highly active and stable AOR electrocatalyst. The unique electron buffering effect of PNW‐C60 enhances the desorption of nitrogen‐containing species and prevents their poisoning on the Pt NPs surface. Consequently, the as‐obtained PNW‐C60‐buffered Pt NPs exhibits a high mass activity of 118 A gPt−1 as well as good stability, outperforming commercial Pt/C and graphene‐supported Pt NPs AOR catalysts. By using covalently bonded two‐dimensional fullerene (C60) polymeric network (PNW‐C60) as unique support of Pt nanoparticles (NPs), we succeed in modulating the binding strengths of the key intermediates in the AOR process owing to the electron transfer between PNW‐C60 and Pt NPs, which can enhance the recombination of NxHy species, avoiding the poisoning of adsorbed nitrogen‐containing species. As a result, the as‐prepared Pt NPs/PNW‐C60 exhibits a high mass activity of 118 A gPt−1 for the AOR as well as remarkable long‐term durability, which is much superior to the commercial Pt/C and graphene‐supported Pt NPs.